2018
DOI: 10.1371/journal.pone.0199104
|View full text |Cite
|
Sign up to set email alerts
|

Co-fermentation of cellobiose and xylose by mixed culture of recombinant Saccharomyces cerevisiae and kinetic modeling

Abstract: Efficient conversion of cellulosic sugars in cellulosic hydrolysates is important for economically viable production of biofuels from lignocellulosic biomass, but the goal remains a critical challenge. The present study reports a new approach for simultaneous fermentation of cellobiose and xylose by using the co-culture consisting of recombinant Saccharomyces cerevisiae specialist strains. The co-culture system can provide competitive advantage of modularity compared to the single culture system and can be tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…Morales-Rodriguez et al 2011, for instance, consider the modified Escherichia coli ATCC-55124 strain in their SSCF model, while Krishnan et al (1999) consider the modified S. cerevisiae 1400(pLNH33) strain. Chen et al (2018) on the other hand modeled a co-fermentation process based on the co-culture of several genetically modified S. cerevisiae strains, each one specialized in metabolizing one particular type of substrate.…”
Section: Simultaneous Saccharification and Co-fermentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Morales-Rodriguez et al 2011, for instance, consider the modified Escherichia coli ATCC-55124 strain in their SSCF model, while Krishnan et al (1999) consider the modified S. cerevisiae 1400(pLNH33) strain. Chen et al (2018) on the other hand modeled a co-fermentation process based on the co-culture of several genetically modified S. cerevisiae strains, each one specialized in metabolizing one particular type of substrate.…”
Section: Simultaneous Saccharification and Co-fermentationmentioning
confidence: 99%
“…For the EJ2-strain, it was found that the initial cellobiose concentration has a major impact on the ethanol production by the recombinant S. cerevisiae strain. Therefore, a S 0 factor was included in the expression for the ethanol production growth rate ν, rendering the following (semiempirical) correlation (Chen et al, 2018): Chen et al 2018noticed that the SR8 strain was unable to uptake xylose when it was only in a small concentration present in the medium. Additionally, when xylose levels were low and xylose consumption had ceased, the consumption of ethanol by the SR8 strain became prevalent.…”
Section: Simultaneous Saccharification and Co-fermentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementary approaches have coupled cellobiose utilization with xylose utilization in recombinant S. cerevisiae with improved xylose to ethanol conversion rates [30]. Recombinant approaches have not yet yielded a successful approach to xylose utilization that overall surpasses the ethanol productivities of native species on glucose; however, work is getting closer [8,14,[31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%